Practicing Feminist Ethics in Psychology. 2000
DOI: 10.1037/10343-009
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues in using self-disclosure in feminist therapy.

Abstract: Validity of the Eating Disorder Examination Questionnaire (EDE-Q) in screening for eating disorders in community samples. Behaviour Research and Therapy, 42, 551-567. http://dx.doi.org/10.1016/S0005-7967(03)00161-X Multi-Service Eating Disorders Association. (2018). Hope and inspiration. Retrieved from https://www.medainc.org/events/hope-inspiration/ Myers, D., & Hayes, J. A. (2006). Effects of therapist general selfdisclosure and countertransference disclosure on ratings of the therapist and session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…At least one study found that, generally, disclosure was perceived as helpful in individual therapy but that the skill of the therapist was paramount in how disclosure was perceived (Hanson, 2005). Client needs are another key factor in determining whether therapist self-disclosure is clinically indicated and ethically grounded (Lerman & Porter, 1990;Mahalik et al;Peterson;Pope & Vasquez, 2007). Requiring a trainee to disclose a disability, or any other traditionally marginalized status, before an initial therapeutic encounter does not permit the trainee and supervisor to develop a clinical rationale specific to that client, as little to nothing is known about the client.…”
Section: Clinical Issuesmentioning
confidence: 99%
“…At least one study found that, generally, disclosure was perceived as helpful in individual therapy but that the skill of the therapist was paramount in how disclosure was perceived (Hanson, 2005). Client needs are another key factor in determining whether therapist self-disclosure is clinically indicated and ethically grounded (Lerman & Porter, 1990;Mahalik et al;Peterson;Pope & Vasquez, 2007). Requiring a trainee to disclose a disability, or any other traditionally marginalized status, before an initial therapeutic encounter does not permit the trainee and supervisor to develop a clinical rationale specific to that client, as little to nothing is known about the client.…”
Section: Clinical Issuesmentioning
confidence: 99%
“…Advocates of feminist theories have openly supported the appropriate use of therapist self-disclosure (Mahalik, VanOrmer, & Simi, 2000), asserting that this intervention helps transmit feminist values, equalizes power, fosters client growth, creates a feeling of solidarity between therapist and client, helps clients feel less shameful, nurtures client liberation, and acknowledges the place of the real relationship between client and therapist. Additionally, therapist self-disclosure about credentials and values can help clients make informed choices about whether they wish to work with a particular therapist.…”
Section: Disclosures Of Immediacymentioning
confidence: 99%
“…Thus, therapists of this orientation may elect to disclose not only some of the factual Therapist Self-Disclosure information cited previously but also may more regularly disclose their beliefs and lifestyles, religious and class backgrounds, sexual orientation, and political views so that potential clients have enough information to make an informed decision regarding selection of a therapist (Mahalik et al, 2000).…”
Section: Use Appropriate Content In Therapist Self-disclosuresmentioning
confidence: 99%
“…Some authors, particularly those operating from feminist and multicultural perspectives, assert that informed consent should be expanded to include clinician disclosures about basic demographic and background information, since the client has the right to know the sort of person with whom she or he will be working (Mahalik, Van Ormer, & Simi, 2000).…”
Section: Ethical Considerationsmentioning
confidence: 99%